Aggregational Attitude of Hexadecyltrimethylammonium Bromide in Aqueous Solutions of Sodium Salt at 298.15k - Medinat, Osundiya Olubunmi; Esan, Olaseni Segun (International Journal of Chemistry and Materials Research, 2016)
This research reports micelle formation of hexadecyltrimethylammonium bromide and the dependence of aggregation number on the array of sodium salts in aqueous solution. Critical micelle concentration, degree of micelle ionization, and aggregation number were obtained from electrical conductivity measurement. Pseudo-phase separation model was used to evaluate and discussed standard Gibb’s free energy of micellization. It was observed that hexadecyltrimethylammonium bromide critical micelle concentration decreases while aggregation number increases. Amongst the sodium salt, disodium hydrogen phosphate was found to have the highest tendency in reducing hexadecyltrimethylammonium bromide critical micelle concentration. The sodium salts with the highest valency anion strongly promote micellization of hexadecyltrimethylammonium bromide, indicating the dependence of aggregation phenomenon on the availability of anion.